Experience and the results of emergency management of the 1957 accident at the Mayak Production Association. (22nd January 2018) - Batorshin, G Sh; Mokrov, Yu G
Abstract: The experience accumulated while dealing with the aftermath of a major nuclear accident (the 'Kyshtym Accident') in 1957 at the Mayak complex in the Southern Urals of Russia is summarised. Information is presented on the causes of the accident, on the radiation environment and radioactive contamination of the affected territory in the critical period, and on the system of emergency management and decision-making adopted when dealing with the accident and its aftermath. The technical and organisational approaches applied and methods used are described, as well as remediation results and the current situation 60 years after the accident. It is demonstrated that the implementation of fairly simple and self-evident organisational and technical solutions gave good results, and that appropriate timely and task-oriented measures were applied. Safety relevant conclusions and recommendations are presented.